Descortinando o transtorno do desenvolvimento da aprendizagem: perspectiva da terapia ocupacional no contexto escolar - Paterra, Izamara Pereira (Universidade Federal de São Carlos, 2023)
The present study aimed to describe the initial stages of the process of elaborating an educational material about children with developmental learning disorders and occupational performance issues. This proposal is justified by the recognition of the ethical commitment of translating and transferring scientific knowledge into actions, such as the preparation of educational material, which can protect and promote benefits to the health and development process and occupations of children in schooling and literacy development stages. The methodological research applied to the development and validation of educational material involved two initial stages: literature review and demand survey. The literature review was carried out in national occupational therapy databases and in the Scientific Electronic Library Online (SCIELO) and aimed to identify previous skills for literacy (at the elementary school level), the strategies and/or assessments used in the school/classroom to identify children with developmental learning disorders (6 to 10 years), selecting studies published in a period of 10 years (January 2012 to January 2022), with texts fully available; those which were not aimed to school environments were excluded, as well as those in editorial and poster formats. The demand survey stage was carried out with 4 teachers from public elementary schools in the cities of Miguelópolis-SP and Sacramento-MG. In the literature review, 55 studies were analyzed that dealt with the contents of: Prior Skills for Literacy; Main Children's Occupations; Strategies and Evaluations and Performance of Occupational Therapy in the School Context. The answers from the interviews generated the analysis and discussion categories: Professional Profile and Work Routine; Knowledge about Developmental learning disorder (Theoretical and Practical) and Didactic Material. The results found in both stages point to the need to create didactic material that offers support to teachers in relation to the theoretical definition of developmental learning disorders, child and occupational development and forms of evaluation that help in the early identification of cases and assist in the creation of strategies in the classroom, with suggestions and adaptations of pedagogical activities and activities/games/plays that offer/encourage the stimulation of child development and occupational performance. It is concluded that the challenges presented by inclusion in education are of a multifactorial, political and historical nature, thus, the proposal of the didactic material is justified by the need to offer possibilities for health promotion and prevention in the school environment.
Unraveling the developmental learning disorder: perspective of occupational therapy in the school context
Keywords: Transtorno do desenvolvimento da aprendizagem; Ocupações infantis; Avaliação; Intervenção; Terapia ocupacional; Developmental learning disorder; Children's occupations; Assessment; Intervention; Occupational therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL